Short Communication Analysis of Antioxidant and Antibiotic Potentiality of the Extract from Molten Butter Residue: Antibiotic Activity of Molten Butter Residue - Rasheeda Khanam (Biological Sciences - PJSIR, 2023)
This research work was drafted to explore the potential of the extract from dairy waste "Molten butter residue" as a source of the antioxidant agent. The dairy waste extract was subjected to estimation of total phenolic content, total anti-oxidation activity, % of DPPH radical scavenging activity and antibiotic activity. It exhibits total phenolic content of 60.11 mg/mL with maximum total antioxidant activity and 99.39% of DPPH scavenging activity when compared to ascorbic acid as a standard. It also shows antibiotic activity against micro-organisms like Bacillus, Streptococcus and Staphylococcus. The antioxidant and antibiotic potentiality of the extract from molten butter residue may be applicable in pharmaceutical field.